Стан мікроклімату в приміщенні для дорощування поросят - Дробот, Сергій Іванович; Drobot, S. I. (Подільський держ. аграрно-технічн. ун-т, 2018)
Встановлено, що мікроклімат в приміщеннях для поросят упродовж року зазнає істотних сезонних коливань, що потрібно враховувати при розробці заходів щодо нормалізації стану повітряного середовища в період їх дорощування. It has been established that the microclimate in the premises for piglets is subject to significant seasonal fluctuations during the year, which should be taken into account when developing measures to normalize the state of the air environment during their growing.
The microclimate in the room for growing piglets
Keywords: теплий і перехідний сезон; warm and the transitional seasons; поросята; piglets; дорощування; rearing; мікроклімат; microclimate